MANAJEMEN PEMBELAJARAN DI MADRASAH DINIYAH PONDOK PESANTREN - M. Arif Khoiruddin; Ahmad Roufiq Mauludi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
This research is aimed to identify learning management of Ihya Ulumiddin Islamic Boarding School. The Boarding school is under the management of Darusallam of Lirboyo. This research design is descriptive qualitative while the data collection method uses are observation, interview and documentation. The stage of teaching plan is done by formulating and analyzing the materials thought. The teacher prepares the materials with mudzakaroh and determines the homeroom teacher. The teaching process is begun by reading nadzhoman together, rois amm of the captain of the class leads and repeats the previous lesson before stating the new lesson, the teacher give time for the students to memorize the materials before presenting it to the teacher. Beside memorizing and musyawaroh, the evaluation stage is done by doing murojaah, a repeating of previous explanation. Students present the result of memorizing based on the schedule given by the homeroom teacher. Sorogan is applied in reading the books which have been meant by the teacher in the previous meeting. The students also answer the questions from the teacher dealing with previous book read. The last point of the management is recruiting the alumni for replacing the teacher who comes home to do the teacher’s jobs as mentioned.